RECENSIÓN: DE OFFICIO SENATORIO ROMANO. KAREN MARÍA VILACOBA RAMOS Thomson Reuters Aranzadi, ISBN 9788411244527, Cizur Menor (Navarra) 2022 - Bartol Hernández, Francisco (Revista de Derecho de la UNED (RDUNED), 2023)
-